Similar or Different Effects? Quantifying the Effects of Humility and Modesty on Job Performance - Peng, He (Frontiers in Psychology, 2022)
Humility and modesty are both emphasized in Eastern and Western societies. However, people usually conflate them in everyday usage. To reduce the confusion of the two constructs, it is very vital to carefully differentiate the two constructs and examine whether they lead to similar or different effects on job performance. In this study, we scrutinized the effects of the two constructs on four dimensions of job performance simultaneously, including task performance, citizenship behavior (helping and voicing), unethical pro-organizational behavior, and innovative behavior. Using a dataset of 239 employees and 77 supervisors, we showed that modesty is not related to task performance and voicing, but that it is positively related to unethical pro-organizational behavior and negatively related to helping and innovative behavior. In contrast, we showed that humility is negatively related to unethical pro-organizational behavior and positively related to task performance, helping, voicing, and innovative behavior. Our findings reveal that modesty and humility can lead to very divergent work outcomes. The results strongly support the idea that modesty and humility are distinct constructs embedded in separate nomological networks and strongly suggest that organizations should encourage employees’ humility rather than modesty. The theoretical and practical implications of this work are discussed.